Unveiling adaptability of the castor (Ricinus communis L.) genotype using AMMI and GGE Models: UNVEILING ADAPTABILITY OF THE CASTOR GENOTYPE USING AMMI AND GGE MODELS - YAMANURA MADIVAL,; R MOHAN KUMAR,; A PRASHANTH,; SANGANNAVAR,; T MANJUNATHA,; C LAVANYA,; S C RANGANATH,; G JADESHA, (Journal of Oilseeds Research, 2025)
This study examined the influence of genotype-environment interaction on seed yield and other complex quantitative traits of castor genotypes. Eight castor genotypes were evaluated across six growing environments during the kharif season of 2020. The field evaluation responses were analyzed using AMMI and GGE biplot methods. The analysis of variance revealed significant differences among genotypes and their interactions with environments, highlighting location-specific performance. The "which won where" pattern from the GGE biplot identified crossover interactions, with vertex genotypes ICH-66, GCH-8, DCS-9, and DCH-519 exhibiting distinct yield trends. Notably, ICH-66 demonstrated broader adaptability and superior performance across both irrigated and rainfed conditions. Its consistent performance across diverse environments highlights its robustness and suitability for commercial cultivation. This study confirmed the wider adaptability, higher productivity, and environmental stability of ICH-66, making it a promising genotype for achieving stable seed yield.